2020
DOI: 10.3390/nu12040900
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Formula Eliminates the Necessity of Bacterial Dysbiosis and Induces Inflammation and Injury in the Paneth Cell Disruption Murine NEC Model in an Osmolality-Dependent Manner

Abstract: Necrotizing enterocolitis (NEC) remains a significant cause of morbidity and mortality in preterm infants. Formula feeding is a risk factor for NEC and osmolality, which is increased by the fortification that is required for adequate growth of the infant, has been suggested as a potential cause. Our laboratory has shown that Paneth cell disruption followed by induction of dysbiosis can induce NEC-like pathology in the absence of feeds. We hypothesized adding formula feeds to the model would exacerbate intestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 70 publications
1
31
0
Order By: Relevance
“…In a Paneth cell disruption NEC rodent model, the addition of formula feeding exacerbated intestinal injury independent of gut microbial dysbiosis [152]. This result emphasized the caution needed for preterm infant feeding.…”
Section: Iga-microbiota In Necrotizing Enterocolitismentioning
confidence: 93%
“…In a Paneth cell disruption NEC rodent model, the addition of formula feeding exacerbated intestinal injury independent of gut microbial dysbiosis [152]. This result emphasized the caution needed for preterm infant feeding.…”
Section: Iga-microbiota In Necrotizing Enterocolitismentioning
confidence: 93%
“…To remove the potential confounding impact of K. pneumoniae use in the Paneth cell disruption model, we also employed our recently described RMS formula-Paneth cell model [40]. In brief, P14-16 mice were given an intraperitoneal injection of 75 µg/kg of dithizone (Sigma-Aldrich, St. Louis, MO, USA) dissolved in 25 mM lithium carbonate or an equivalent volume of lithium carbonate alone as a vehicle control.…”
Section: Nec Modelsmentioning
confidence: 99%
“…Ileal intestinal injury scoring was performed by a single blinded investigator as previously described [38][39][40]42,43]. In brief, the distal 1/3 of the intestine just before the cecum was harvested and then fixed in 10% buffered formalin, embedded in paraffin, and then sectioned at five µm thickness.…”
Section: Injury Scoringmentioning
confidence: 99%
“…15 A recent animal study showed increased inflammation and intestinal injury in mice fed on hyperosmolar feeds compared with controls. 16 We have studied the change in osmolality when medications and fortifiers were added to milk feeds and water. The freezing-point depression method was used to derive a neat osmolality measure of medications and diluents (water, breast milk, fortified breast milk, and formula milk) separately and then in combination.…”
Section: Introductionmentioning
confidence: 99%
“…The American Academy of Pediatrics has recommended an osmolality not exceeding 450 mOsm/kg for preterm milk feeds to curtail the risk of NEC 15 . A recent animal study showed increased inflammation and intestinal injury in mice fed on hyperosmolar feeds compared with controls 16 . We have studied the change in osmolality when medications and fortifiers were added to milk feeds and water.…”
Section: Introductionmentioning
confidence: 99%